PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE GUIDED NOTE TAKING (GNT) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMP NEGERI 34 PADANG - Armelia, Yuma; Rahmi, Rahmi; Lovia, Lita (STKIP PGRI Sumbar, 2013)
This research is based by the understanding of mathematical concept that still low for some student. Student also lack of understanding every material that they noted. This research is also to find out how the development the understanding of student mathematical concept with applying the active learning strategy